Acceptance model and use of service in Jordanian telecommunication sector - Alnawafleh, Enas Ali Theeb; Universiti Sultan Zainal Abidin . Faculty of Business and Management (2021)
The emergence ofInformation and Communication Technology (lCT) has significantly
improved the quality of life for people around the world. This emergence has resulted
in a competitive scenario amongst service providers in supplying services of quality to
satisfy customers. ICT providers are investing large funds into research and
development to gain a competitive edge. Moreover, a reduction in prices of services by
telecommunication companies has led to a decrease in their net profits and revenues.
Although many studies have been accomplished to develop the theoretical models of
technology adoption, studies on the acceptance of service is still scarce. Currently, the
model for customers' intention to subscribe to a particular service provider is of
considerable interest to stakeholders. This study aims to develop an integrated
Technology Adoption Model (T AM2) and service quality for telecommunication sector
in Jordan. Four hundred and twenty (420) potential customers from three main
telecommunication companies operating in Jordan; namely Zain, Orange and Urnniah,
were recruited using a convenience sampling method. Subsequently, 400 completed
questionnaires were retrieved, giving a response rate of 95.2% of the original sample.
The data was collected in one month; at the beginning of June 2020. The Structural
Equation Model (SEM) using the IBM SPSS AMOS 22.0 was applied to the dataset to
test the proposed hypotheses. The analysis result concluded that service quality,
perceived usefulness, perceived ease of use and subjective norms have a significant
positive effect on attitude towards service and intention to use service. In addition,
attitude towards service is also significantly related to intention to use service. There is
a negative relationship between perceived ease of use and perceived usefulness. From
a total often direct effect hypotheses in this study, nine were supported while one was
not. Similarly, attitude towards service does act as a mediator in the relationship
between service quality, perceived usefulness and subjective norms and intention to use
service. From the three moderator effect hypotheses, only one was supported. The
finding of this study to be a baseline to improve the usage of services of the
telecommunication companies in terms of understanding the preferences and attitude of
customers about the services. This study contributes to the ICT research from both
theoretical and practical perspectives. Theoretically, it showed the significance of
service quality as a predictor of T AM2 in the Jordanian telecommunication companies.
Practically, this model enabled all the stakeholders to understand factors influencing
customers' intention to use service in their activities. Finally, the study calls for
researchers to use the integrated model based on employees of mobile phone service
providers. It would be valuable to test the developed integrated TAM2 model in other
e-commerce domains.
1. Intrductiuon -- 2. Literature review -- 3. Research methodology -- 4. Data analysis ang findings -- 5. Discussion and conclusion
Thesis (Degree of Doctor of Philosophy) - Universiti Sultan Zainal Abidin, 2021
Includes bibliographical references (leaves 243-313) and index
Keywords: Universiti Sultan Zainal Abidin -- Faculty of Business and Management -- Dissertations; Universiti Sultan Zainal Abidin -- Dissertations; Dissertations, Academic; Telecommunication; Telecommunication -- Jordan